The 24-hour customer : new rules for winning in a time-starved, always-connected economy - Ott, Adrian C. (New York : HarperBusiness, 2010)
'From the CEO and founder of a top Silicon Valley-based consulting firm, a powerful new book that challenges businesses to reconceive their approaches to time and technology--and win an unprecedented share of their customers' time, attention, and money'--Provided by publisher.
Includes bibliographical references (p. [199]-215) and index.
Keywords: Customer services; Time management